Detection of Lymphovascular Invasion by D2-40 (Podoplanin) Immunoexpression in Endometrial Cancer. Issue 8 (1st October 2012) - Weber, Sarah K.; Sauerwald, Axel; Pölcher, Martin; Braun, Michael; Debald, Manuel; Serce, Nuran Bektas; Kuhn, Walther; Brunagel-Walgenbach, Giesela; Rudlowski, Christian
Abstract : Background: Lymph node involvement is a major feature in tumor spread of endometrial cancer and predicts prognosis. Therefore, evaluation of lymph vessel invasion (LVI) in tumor tissue as a predictor for lymph node metastasis is of great importance. Immunostaining of D2-40 (podoplanin), a specific marker for lymphatic endothelial cells, might be able to increase the detection rate of LVI compared with conventional hematoxylin-eosin (H-E) staining. The aim of this retrospective study was to analyze the eligibility of D2-40–based LVI evaluation for the prediction of lymph node metastases and patients' outcome. Patients and Methods: Immunohistochemical staining with D2-40 monoclonal antibodies was performed on paraffin-embedded tissue sections of 182 patients with primary endometrioid adenocarcinoma treated in 1 gynecologic cancer center. Tumors were screened for the presence of LVI. Correlations with clinicopathological features and clinical outcome were assessed. Results: Immunostaining of D2-40 significantly increased the frequency LVI detection compared with conventional H-E staining. Lymph vessel invasion was identified by D2-40 in 53 (29.1%) of 182 tumors compared with 34 (18.3%) of 182 carcinomas by routine H-E staining ( P = 0.001). D2-40 LVI was detectable in 81.0% (17/21) of nodal-positive tumors and significantly predicted lymph node metastasis ( P = 0.001). Furthermore, D2-40 LVI was an independent prognostic factor for patients overall survival considering tumor stage, lymph node involvement, and tumor differentiation ( P < 0.01). D2-40–negative tumors confined to the inner half of the myometrium showed an excellent outcome (5-year overall survival, 97.8%). Conclusions: D2-40–based LVI assessment improves the histopathological detection of lymphovascular invasion in endometrial cancer. Furthermore, LVI is of prognostic value and predicts lymph node metastasis. D2-40 LVI detection might help to select endometrial cancer patients who will benefit from a lymphadenectomy.